Erlangen pipe flow: the concept and DNS results for microflow control of near-wall turbulence - Lammers, Peter; Jovanovic, Jovan; Frohnapfel, Bettina; Delgado, Antonio (Microfluidics and Nanofluidics, 2012)
The concept of a micropatterned surface morphology capable of producing self-stabilization of turbulence in wall-bounded flows is considered in pipes of non-circular cross-sections which act to restructure fluctuations towards the limiting state where these must be entirely suppressed. Direct numerical simulations of turbulence in pipes of polygon-shaped cross-sections with straight and profiled sides were performed at a Reynolds number Res ' 300 based on the wall shear velocity and the hydraulic diameter. Using the lattice Boltzmann numerical algorithm, turbulence was resolved with up to 540 * 10 6 grid points (8;192 * 257 * 256 in the x 1, x 2 and x 3 directions). The DNS results show a decrease in the viscous drag around corners, resulting in a reduction of the skin-friction coefficient compared with expectations based on the wellestablished concept of hydraulic diameter and the use of the Blasius correlation. These findings support the conjecture that turbulence might be completely suppressed if the pipe cross-section is a polygon consisting of a sufficient number of profiled sides of the same length which intersect at right angles at the corners. © Springer-Verlag 2012.
UnivIS-Import:2015-03-09:Pub.2012.tech.ITC.stmmec.erlang

Experimental in-situ investigations of turbulence under high pressure - Song, Kwonyul; Al-Salaymeh, Ahmed; Jovanovic, Jovan; Rauh, Cornelia; Delgado, Antonio (In Proceedings of the 5th International Conference on High Pressure Bioscience and Biotechnology, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.ITC.stmmec.experi_2

Experimental in situ investigations of turbulence under high pressure - Song, Kwonyul; Al-Salaymeh, Ahmed; Jovanovic, Jovan; Rauh, Cornelia; Delgado, Antonio (Annals of the New York Academy of Sciences, 2010)
In tube injection systems applied in high-pressure processing of packed biomaterials and foods, the pressure-transmitting medium is injected into the vessel to increase the pressure up to 1000 MPa, generating a submerged liquid-free jet. The presence of a turbulent-free jet during the pressurization phase and its positive influence on the homogeneity of the product treatment has already been examined by computational fluid dynamics investigations. However, no experimental data have supported the existence and properties of turbulent flow under high-pressure (HP) conditions up to 400 MPa. This contribution presents the development of two experimental setups: HP-laser Doppler anemometry and HP-hot wire anemometry. For the first time the time-averaged velocity profiles of a free jet during pressurization up to 300 MPa at different Reynolds numbers (Re) have been obtained. In this article, the dependence of the velocity profiles on the Re is discussed in detail. Moreover, the relaminarization phenomenon of the turbulent pipe flow most likely caused by the compressibility effects and viscosity changes of the pressure-transmitting medium is examined. © 2010 New York Academy of Sciences.
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.experi_4
Keywords: High pressure; Hotwire anemometry; Laser Doppler anemometry; Turbulence

Experimental investigation of viscous drag reduction by flow control of laminar to turbulent transition using microgroove surface pattern - Jovanovic, Jovan; Frohnapfel, Bettina; Lienhart, Hermann; Delgado, Antonio (Proceedings of the 8th International ERCOFTAC Symposium on Engineering Turbulence Modelling and Measurements, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.experi_1

Experimental investigations of turbulent drag reduction by surface-embedded grooves - Frohnapfel, Bettina; Jovanovic, Jovan; Delgado, Antonio (Journal of Fluid Mechanics, 2007)
Consideration of near-wall turbulence in the functional space that emphasizes the level of anisotropy of the velocity fluctuations not only provides an understanding of th causative physics behind remarkable effects of turbulent drag reduction, but also lead to the logical design of a surface topology which is shown experimentally to be capable of producing a significant reduction of viscous drag which far exceeds what has been achieved so far. © 2007 Cambridge University Press.
UnivIS-Import:2015-03-09:Pub.2007.tech.ITC.stmmec.experi_6

Hydraulic model of the skin friction reduction with surface grooves - Frohnapfel, Bettina; Jovanovic, Jovan; Lammers, Peter; Delgado, Antonio (Springer, 2008)
The reduction of skin friction in turbulent flows holds considerable promise for energy savings. The present work shows how and why skin friction and the dissipation are interrelated in turbulent channel flows. A hydraulic model formulation is presented for the skin friction reduction that can be obtained with a surface structure recently proposed for flow control. The model predictions are validated with results from direct numerical simulations. © 2008 Springer.
UnivIS-Import:2015-04-16:Pub.2008.tech.ITC.stmmec.hydrau
Keywords: Flow control; Skin friction reduction; Surface structures

In situ investigation of the turbulent-laminar transition of temperature fluctuations during pressure building up to 300MPa - Song, Kwonyul; Regulski, Wojciech; Jovanovic, Jovan; Rauh, Cornelia; Delgado, Antonio (High Pressure Research, 2009)
The investigation of fluid flow under high pressure up to 300MPa has been developing extensively during recent years [M. Pehl, F. Werner, and A. Delgado, First visualization of temperature fields in liquids at high pressure using thermochromic liquid crystals, Exp. Fluids 29(3) (2000), pp. 302-304; P. Kitsubun, C. Hartmann, and A. Delgado, Numerical investigations of process heterogeneities during high hydrostatic pressure treatment with turbulent inflow conditions, Proc. Appl. Math. Mech. 5 (2005), pp. 573-574; K. Song, C. Rauh, and A. Delgado, Experimental in-situ investigations on fluid flow during high pressure processing by means of LDA and HWA, Proc. Appl. Math. Mech. 8 (2008), pp. 10603-10604; K. Song, A. Al-Salaymeh, J. Jovanovic, C. Rauh, and A. Delgado, Experimental in-situ investigations of turbulence under high pressure, Ann. NY Acad. Sci. (2010), in press]. The range of application of high-pressure technologies spreads from food processing through chemical, bio-chemical and pharmaceutical applications, to mechanical engineering. This results in a high demand for experimental data as well as theoretical backgrounds of various phenomena occurring in the fluids during high-pressure processes. Up-to-date research shows that the properties of many substances and the phenomena occurring under increased pressure differ significantly from their properties in ambient conditions. Song et al. showed for the first time that a sudden increase of pressure in liquids can completely re-laminarize the turbulent flow [K. Song, C. Rauh, and A. Delgado, Experimental in-situ investigations on fluid flow during high pressure processing by means of LDA and HWA, Proc. Appl. Math. Mech. 8 (2008), pp. 10603-10604; K. Song, A. Al-Salaymeh, J. Jovanovic, C. Rauh, and A. Delgado, Experimental in-situ investigations of turbulence under high pressure, Ann. NY Acad. Sci. (2010), in press]. This paper focuses on the investigation of the fluctuations in a liquid's temperature field during the pressure build-up phase. A 1.5L pressure autoclave is fed with silicon oil, hexamethyldisiloxane, via a nozzle with a diameter of 1.6mm. The investigation using high-pressure-hotwire anemometry concerns the free jet flowing out from the nozzle into the vessel. The pressure of 300MPa is reached within 52s, the temperature due to the compression increases from 18°C to 50°C, and the Reynolds number varies from 10,000 to 2000. Initially, the fully turbulent flow starts to be damped by increasing viscous forces, which grow due to the pressure ramp. When viscous forces prevail over fluid's inertia, the turbulence can break down. The transition in the temperature field from turbulence to laminar occurs at the level of Re ≈ 3600, which is typical for turbulent flows. The results show great regularity in the occurrence of the turbulence break-down due to the increase of viscosity and compressibility effects. The other critical parameters for the turbulence-laminar transition are also obtained. The knowledge gathered in the experiments could be adapted in various fields of industry. For example, in IC-engines, it would enable keeping a fully laminar flame, thus controlling the combustion better and obtaining better efficiency. On the other hand, when the laminarization is undesired, e.g. in food processing, the turbulence in a high-pressure vessel assures more uniform pasteurization, thus such conditions could be avoided.
UnivIS-Import:2015-03-09:Pub.2009.tech.ITC.stmmec.insitu
Keywords: High pressure; Hotwire anemometry; Laser-Doppler anemometry; Turbulence

In-situ investigation of turbulent fluid flow under high pressure conditions by means of Laser Doppler Anemometry and numerical simulation - Song, Kwonyul; Jovanovic, Jovan; Al-Salaymeh, Ahmed; Rauh, Cornelia; Delgado, Antonio; Han, Y. (Proceedings der 17. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.ITC.stmmec.insitu_0

Interpretation of the mechanism responsible for the persistence of a laminar region in turbulent duct flow - Daschiel, Gerti; Frohnapfel, Bettina; Jovanovic, Jovan (ETC 2013 - 14th European Turbulence Conference, 2013)
The flow field in an isosceles triangular duct with a small apex angle of 11.5◦ is investigated using direct numerical simulation at the hydraulic Reynolds number Reh = 4500. Within the duct cross-section regions with essential laminar and turbulent properties are found to exist next to each other. From analysis of this flow field we gain insights into the mechanisms responsible for the flow laminarisation towards the corner of the duct, which leads to a significant reduction of the skin friction. In addition, further investigations of the disturbances appearing in the laminar part of the flow domain indicate a possible application of corners for the delay of laminar to turbulent transition in duct flows.
CRIS-Team Scopus Importer:2020-03-17

LDA measurements of Reynolds stresses in a swirling turbulent pipe flow - Genc, Balkan; Ertunc, Özgür; Jovanovic, Jovan; Delgado, Antonio (Advances in Turbulence XII - Proceedings of the 12th EUROMECH European Turbulence Conference, 2009)
UnivIS-Import:2017-12-18:Pub.2009.tech.ITC.stmmec.ldamea_2

LDA Messungen von Rohrströmungen mit Drall für einen breiten Bereich von Drallzahlen - Genc, Balkan; Ertunc, Özgür; Jovanovic, Jovan; Delgado, Antonio (Proceedings der 17. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik, 2009)
UnivIS-Import:2017-12-18:Pub.2009.tech.ITC.stmmec.ldames

Microflow-based control of near-wall fluctuations for large viscous drag reduction - Jovanovic, Jovan; Srikantharajah, Rubitha; Lienhart, Hermann; Delgado, Antonio; Frohnapfel, Bettina; Jovanović, Djordje (Microfluidics and Nanofluidics, 2011)
The stabilizing effect of microgroove surface morphology on viscous drag reduction was studied experimentally in the inlet region of a plane channel flow. The stabilization is thought to be due to the ability of a microgrooved surface pattern to suppress the velocity fluctuations in the spanwise direction on a restricted portion of the wetted surface, which prevents vorticity development at the wall and consequently across the entire flow field. This smart microflow control strategy, which works successfully only under very particular circumstances, was implemented in a microgroove-modified channel flow in which the front part has a microgrooved surface topology. The results of pressure drop measurements indicate that microgrooved surfaces can effectively stabilize laminar boundary layer development, leading to a significant reduction in the viscous drag. In the rear flat part of the microgroove-modified channel test section, a maximum drag reduction of DR ≃ 35% was measured. This corresponds to an overall drag reduction of DR ≃ 16% at a length Reynolds number of Re x ≃ 10 6: The drag reduction effect persisted in a narrow range of flow velocities and for the reported experimental conditions corresponds to microgroove dimensions between 1.5 and 2.5 viscous length-scales. © Springer-Verlag 2011.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.microf
Keywords: microflow; drag; control

Numerical experiments on flow control of near-wall turbulence - Lammers, Peter; Jovanovic, Jovan; Delgado, Antonio (PAMM, 79th Annual Meeting of the International Association of Applied Mathematics and Mechanics (GAMM), 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.ITC.stmmec.numeri_6

Numerical experiments on flow control of near-wall turbulence - Lammers, Peter; Jovanovic, Jovan; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2008)
UnivIS-Import:2018-09-05:Pub.2008.tech.ITC.stmmec.numeri_0

Numerical experiments on self-control of wall turbulence by surface morphology - Lammers, Peter; Jovanovic, Jovan; Frohnapfel, Bettina; Delgado, Antonio (7th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2011, 2011)

Numerical simulation of turbulent flow through Schiller's wavy pipe - Daschiel, Getraud; Krieger, Veronika; Jovanovic, Jovan; Delgado, Antonio (Journal of Fluid Mechanics, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.ITC.stmmec.numeri_6
Keywords: turbulence control; flow control; drag reduction

On the mechanism responsible for turbulent drag reduction by dilute addition of high polymers: Theory supported by LDA measurements - Jovanovic, Jovan; Genc, Balkan; Delgado, Antonio; et al. (Proceedings der 18. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2010)
UnivIS-Import:2017-12-18:Pub.2010.tech.ITC.stmmec.onthem

On unified boundary conditions for improved predictions of near-wall turbulence - Jakirlic, S.; Jovanovic, Jovan (Journal of Fluid Mechanics, 2010)
A novel formulation of the wall boundary conditions relying on the asymptotic behaviour of the Taylor microscale λ and its relationship to the homogeneous part of the viscous dissipation rate of the kinetic energy of turbulence ∈h =5q2/λ2, applicable to near-wall turbulence, is examined. The linear dependence of λ on the wall distance in close proximity to the solid surface enables the wall-closest grid node to be positioned immediately below the edge of the viscous sublayer, leading to a substantial coarsening of the grid resolution. This approach provides bridging of a major portion of the viscous sublayer, higher grid flexibility and weaker sensitivity against the grid non-uniformities in the near-wall region. The performance of the proposed formulation was checked against available direct numerical simulation databases of complex wall-bounded flows featured by swirl and separation. © 2010 Cambridge University Press.
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.onunif
Keywords: turbulence modelling; wall-bounded flows

Persistence of turbulent flow in microchannels at very low Reynolds numbers - Lammers, Peter; Jovanovic, Jovan; Delgado, Antonio (Microfluidics and Nanofluidics, 2011)
A fully resolved numerical simulation of a turbulent microchannel flow, with uniformly spaced twodimensional obstruction elements mounted at the wall and normal to the flow direction, was carried out at a very low Reynolds number ofRe 970 based on the centerline velocity and themicrochannel height.Employing the latticeBoltzmann numerical technique, all energetic scales of turbulence were resolved with about 19 × 10 6 grid points (1261 × 129 × 128 in the x 1, x 2, and x3 directions). The simulated results confirm the self-maintenance of turbulence at such a low Reynolds number. Turbulence persisted over more than 1,000 turnover times, which was sufficiently long to prove its self-maintenance. These findings support the conjecture that turbulence developing in microchannels having rough walls can not only be initiated but alsomaintained at very lowReynolds numbers. © Springer-Verlag 2011.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.persis

Relaminarization of wall turbulence by high-pressure ramps at low reynolds numbers - Song, Kwonyul; Jovanovic, Jovan; Al-Salaymeh, Ahmed; Rauh, Cornelia; Delgado, Antonio (Thermal Science, 2016)
Reverse transition from the turbulent towards the laminar flow regime was investigated experimentally by progressively increasing the pressure up to 400 MPa in a fully developed pipe flow operated with silicone oil as the working fluid. Using hot-wire anemometry, it is shown indirectly that at low Reynolds numbers a rapid increase in pressure modifies the turbulence dynamics owing to the processes which induce the effects caused by fluid compressibility in the region very close to the wall. The experimental results confirm that under such circumstances, the traditional mechanism responsible for self-maintenance of turbulence in wall-bounded flows is altered in such a way as to lead towards a state in which turbulence cannot persist any longe
UnivIS-Import:2018-02-22:Pub.2016.tech.ITC.stmmec.relami
Keywords: High pressure ramp; Relaminarization; Wall turbulence

Reverse transition of turbulent pipe flow by high pressure - Song, Kwonyul; Jovanovic, Jovan; Rauh, Cornelia; Wierschem, Andreas; Delgado, Antonio (Proceedings der 18. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.revers

The holy grail of microfluidics: sub-laminar drag by layout of periodically embedded microgrooves - Daschiel, Gerti; Peric, Milovan; Jovanovic, Jovan; Delgado, Antonio (Microfluidics and Nanofluidics, 2013)
The sub-laminar drag effect of microgroove surfaces was studied numerically in a steady two-dimensional channel flow at subcritical Reynolds numbers. Considerations are restricted to grooves of a few viscous length scales in depth, which are assumed not to promote the laminar to turbulent transition process. It was found that the drag reduction effect is due to the layout of grooves with respect to the flow direction and contour geometry. Results of computations show that for grooves of curved contour placed normal to the flow direction, drag arising from viscous and pressure forces is modulated due to the functional dependence of forces on the surface area projected in the flow direction. Such a groove layout leads to a large skin-friction reduction, but a comparable increase in pressure drag results in sub-laminar drag if drag over flat surface is considered as a reference. For a curved groove contour, the drag reduction increases with increasing Reynolds number and reaches about 5 % at Reynolds numbers approaching critical. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.tech.ITC.stmmec.thehol
Keywords: Drag reduction surfaces; Flow control; Viscous drag reduction; Viscous flow; Wall-bounded flows

The structure of turbulence in a swirling pipe flow - Jovanovic, Jovan; Pashtrapanska, Mira; Lienhart, Hermann; Delgado, Antonio (PAMM, 79th Annual Meeting of the International Association of Applied Mathematics and Mechanics (GAMM), Bremen 2008, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.ITC.stmmec.thestr

Toward design of the antiturbulence surface exhibiting maximum drag reduction effect - Krieger, Veronika; Peric, Robinson; Jovanovic, Jovan; Lienhart, Hermann; Delgado, Antonio (Journal of Fluid Mechanics, 2018)
The flow development in a groove-modified channel consisting of flat and grooved walls was investigated by direct numerical simulations based on the Navier-Stokes equations at a Reynolds number of based on the full channel height and the bulk velocity. Simulations were performed for highly disturbed initial flow conditions leading to the almost instantaneous appearance of turbulence in channels with flat walls. The surface morphology was designed in the form of profiled grooves aligned with the flow direction and embedded in the wall. Such grooves are presumed to allow development of only the statistically axisymmetric disturbances. In contrast to the rapid production of turbulence along a flat wall, it was found that such development was suppressed over a grooved wall for a remarkably long period of time. Owing to the difference in the flow structure, friction drag over the grooved wall was more than 60Â % lower than that over the flat wall. Anisotropy-invariant mapping supports the conclusion, emerging from analytic considerations, that persistence of the laminar regime is due to statistical axisymmetry in the velocity fluctuations. Complementary investigations of turbulent drag reduction in grooved channels demonstrated that promotion of such a state across the entire wetted surface is required to stabilize flow and prevent transition and breakdown to turbulence. To support the results of numerical investigations, measurements in groove-modified channel flow were performed. Comparisons of the pressure differentials measured along flat and groove-modified channels reveal a skin-friction reduction as large as owing to the extended persistence of the laminar flow compared with flow development in a flat channel. These experiments demonstrate that early stabilization of the laminar boundary layer development with a grooved surface promotes drag reduction in a fully turbulent flow with a preserving magnitude as the Reynolds number increases.
UnivIS-Import:2018-09-05:Pub.2018.tech.ITC.stmmec.toward
Keywords: drag reduction; turbulence control; turbulence modelling

Turbulent dissipation in drag reduced flows - Frohnapfel, Bettina; Jovanovic, Jovan; Delgado, Antonio (Advances in turbulence XI : proceedings of the 11th EUROMECH European Turbulence Conference, 2007)
UnivIS-Import:2018-09-06:Pub.2007.tech.ITC.stmmec.turbul

Viscous drag reduction with surface-embedded grooves - Jovanovic, Jovan; Frohnapfel, Bettina; Delgado, Antonio (Notes on Numerical Fluid Mechanics and Multidisciplinary Design. Turbulence and Interactions. Proceedings the TI 2009 Conference, 2010)
Turbulent drag reduction in wall-bounded flows is investigated experimentally by considering the dynamic effects provoked by large variation of anisotropy in the velocity fluctuations. Deductions based on the analysis of near-wall turbulence lead to the design of the grooved surface topology, for which it is demonstrated experimentally that it can produce a maximum drag reduction of DR ≃ 25%. The drag reduction effect persisted in a narrow range of flow velocities and for the reported experimental conditions corresponds to groove dimensions of about 0.8 viscous length-scale. © 2010 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.viscou